Rhizopus Stem Rot of Orobanche aegyptiaca caused by Rhizopus oryzae in China. Issue 10 (31st May 2013) - Zhang, Xuekun; Yao, Zhaoqun; Zhao, Sifeng; Xie, Huiqin; Yang, Mei
Abstract: Stem rot was recorded on Orobanche aegyptiaca in Shihezi City, Xinjiang Uygur Autonomous Region, China from 2010 to 2011. The pathogen was isolated repeatedly from the infected stems and was identified as Rhizopus oryzae based on morphology, cultural features and molecular analysis. Koch's postulates were supported by pathogenicity tests conducted on healthy plants grown on processing tomato and melon. To our knowledge, this paper is the first to report the occurrence of R. oryzae stem rot on O. aegyptiaca .